2013
DOI: 10.1186/1756-0500-6-176
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of human corneal endothelial cell culture: density dependency of successful cultures in vitro

Abstract: BackgroundGlobal shortage of donor corneas greatly restricts the numbers of corneal transplantations performed yearly. Limited ex vivo expansion of primary human corneal endothelial cells is possible, and a considerable clinical interest exists for development of tissue-engineered constructs using cultivated corneal endothelial cells. The objective of this study was to investigate the density-dependent growth of human corneal endothelial cells isolated from paired donor corneas and to elucidate an optimal seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 19 publications
3
71
0
2
Order By: Relevance
“…Confluent cultures result in a more differentiated phenotype and therefore better suitability for metabolism studies (Ramaiahgari et al 2014). In the case of proliferating cells, such as mesenchymal stem cells, low seeding cell densities ensure good proliferation and expansion of the culture (Fossett and Khan 2012;Peh et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Confluent cultures result in a more differentiated phenotype and therefore better suitability for metabolism studies (Ramaiahgari et al 2014). In the case of proliferating cells, such as mesenchymal stem cells, low seeding cell densities ensure good proliferation and expansion of the culture (Fossett and Khan 2012;Peh et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that it was possible to obtain the hexagonal morphology of the cells at the end of third passage and the count of up to 2.5 3 10 7 cells with a seeding density of greater than or equal to 1 3 10 4 cells per cm 2 [33]. However, after defining the seeding density, the same group also described a novel dual-media approach for the expansion of primary HCECs in vitro.…”
Section: Cultivation Of the Primary Human Donor Corneal Cells Using Amentioning
confidence: 99%
“…A study by Peh et al [33] demonstrated that the outcome of culturing primary HCECs and proliferative potential can be successful if negatively impacted by lower, suboptimal plating density. The study showed that it was possible to obtain the hexagonal morphology of the cells at the end of third passage and the count of up to 2.5 3 10 7 cells with a seeding density of greater than or equal to 1 3 10 4 cells per cm 2 [33].…”
Section: Cultivation Of the Primary Human Donor Corneal Cells Using Amentioning
confidence: 99%
“…[5][6][7][8] Scientists have managed to cultivate human corneal endothelial cells (HCECs) using special media and techniques. [9][10][11] The focus now is on the prospect of the transfer of these cells to the anterior chamber of a living eye. Thus far, cultivated HCEC have been used in animal models.…”
mentioning
confidence: 99%